Meteorological observations at Syowa Station in 2018 by the 59th Japanese Antarctic Research Expedition - Nobumasa Sugiyama; Kohshiro Dehara; Sho Shimamura; Shogo Tanaka; Genki Tsuda (National Institute of Polar Research, 2022)
This report describes the results of meteorological observations at Syowa Station from February 1st, 2018 to January 31st, 2019, carried out by the Meteorological Observation Team of the 59th Japanese Antarctic Research Expedition (JARE-59). The observation methods and instruments, statistical methods used by JARE-59 were almost the same as those used by the JARE-58 observation team. Topics during the period of JARE-59 are as follows. 1) Updated the Meisei Electric RS-06G type GPS radiosonde to the Meisei Electric RS-11G type GPS radiosonde from March 20, 2018. 2) Started to report observation data to the lead center of GRUAN (GCOS Reference Upper Air Network), a high-precision, continuous upper air observation network. 3) Strengthening of upper air observation in cooperation with YOPP-SH (Year Of Polar Prediction in the Southern Hemisphere). 4) Confirmed seven times SODs (Surface Ozone Depletions) were appeared.